Strategi Komunikasi Badan Kependudukan dan Keluarga Berencana Nasional (BKKBN) - Herdiana Ayu Susanti (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2015)
This study aims to determine communication strategy of Population and Family Planning Agency (BKKBN) Special Region of Yogyakarta in disseminating Generation Program Planning (GenRe). The study uses descriptive qualitative method. The result shows that communication strategy undertaken by BKKBN Yogyakarta Province in disseminating the program GenRe is through Student Ambassador Selection genre, GenRe Goes To School and GenRe Goes To Campus, Genre Comedy Competition, Poster Competition genre, and Competition NGE - rap genre. BKKBN also uses mass media as a medium of socialization such as Public Service Announcements on television and radio, internet media by creating a website, blog, facebook, and twitter, as well as the use of billboards appeal board. BKKBN also works with schools and colleges to form the Youth Information and Counseling Center / Student (PIK R/M) to get closer to teenagers and college students.